Antifertility Effect of the Aqueous Alcoholic and Petroleum Ether Extract of Cascabella thevetia L Fruit in Female Albino Rats - Varsha S Zade, Dr (International Journal of Pharmaceutical & Biological Archive, 2015)
Antifertility Effect of the Aqueous Alcoholic and Petroleum Ether Extract of Cascabella thevetia L Fruit in Female Albino Rats